2009
DOI: 10.1210/jc.2008-2662
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Insulin-Like Growth Factor (IGF) I and IGF Binding Protein-3 and Lung Function

Abstract: In conclusion, higher IGF-I levels were associated with higher lung volumes in men, whereas in women this association was only detectable in subjects older than 50 yr. Higher IGF-I values were not associated with increased respiratory muscle strength measured as maximal inspiratory pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…In multivariate analyses of ARDS case status, the APACHE III score excluded P a O 2 /F i O 2 to avoid collinearity (17). Given evidence that sex hormones may be an effect modifier, exogenous estrogen or progestin use at the time of hospital admission was also considered (7). Time-to-measurement of the biomarkers was also added to all multivariate models to assess for possible confounding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In multivariate analyses of ARDS case status, the APACHE III score excluded P a O 2 /F i O 2 to avoid collinearity (17). Given evidence that sex hormones may be an effect modifier, exogenous estrogen or progestin use at the time of hospital admission was also considered (7). Time-to-measurement of the biomarkers was also added to all multivariate models to assess for possible confounding.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of the IGF pathway in fibrotic lung disease have shown increases in lung levels of IGF1 and IGFBP3. IGF1 also plays a critical role in fetal lung development, and IGF-mediated postnatal lung growth is associated with increased alveolar numbers and size (7). …”
Section: Introductionmentioning
confidence: 99%
“…higher lung volumes in men of all ages and women older than 50 years. IGF-1 serum values or increasing lung volumes were not associated with increased strength of respiratory muscles [26].…”
Section: Glaser Et Al Reported a Positive Association Between Igf-1 mentioning
confidence: 73%
“…Therefore, some authors demonstrated in male volunteers with high IGF-1 levels ratio values higher FEV1 and FVC values [26].…”
Section: Glaser Et Al Reported a Positive Association Between Igf-1 mentioning
confidence: 97%
“…In acromegalic patients, respiratory disorders are an important cause of impaired physical performance, contributing to 25% of all patient deaths 1 ) . In this condition, both the upper and lower airways are involved as a result of the changes that affect the craniofacial structure, the geometry of the rib cage, and lung volumes 1 , 14 ) . Respiratory muscle dysfunction has also been described 15 , 16 ) .…”
Section: Introductionmentioning
confidence: 99%